Cicada parasitic moths from China (Lepidoptera: Epipyropidae): morphology, identity, biology, and biogeography. Issue 4 (19th May 2018) - Liu, Yunxiang; Yang, Zhaofu; Zhang, Guoyun; Yu, Qingqing; Wei, Cong
Abstract : Species of the family Epipyropidae are infrequently collected due to their ectoparasitic lifestyle and have therefore received little study. Based on our morphological and molecular analyses, all specimens found parasitizing different species of cicadas in China belong to one species, Epipomponia nawai (Dyar). The species Epipomponia oncotympana Yang (nom. invalid.) was found to be identical with E. nawai . The morphology of the egg, larva, pupa, and adult of E. nawai is described, including the ultrastructure of the egg and larva. Seven types of sensilla and their distribution pattern on the antennae of both females and males of E. nawai are examined using scanning electron microscopy, resulting in a better understanding of sexual dimorphism in this species. Population differentiation and phylogenetic relationships amongst populations of E. nawai occurring in China, the Korean Peninsula, and Japan are analysed. The intraspecific genetic distances suggest a low genetic differentiation which is also consistent with the minor morphological variations. The biogeographic analysis reveals that the Qinling Mountain Range, which is geographically the border of the subtropical and temperate zones, is presumably one of the most important geographic barriers to the gene flow of E. nawai . Our molecular phylogenetic analysis based on the COI gene of E. nawai indicates that frequent gene flow might have occurred in the China mainland, Taiwan and Japan islands, and possibly also the Ryukyu Islands after the Quaternary ice ages. In addition, the biology and behaviour of both larvae and adults of E. nawai were also observed, and results indicate the possibility of bisexual reproduction in this moth. Our results increase the understanding of the morphology, diversity, distribution, and biology of this unusual moth, and should aid future studies on patterns of population differentiation, biogeography, and reproductive behaviour in other epipyropids.